Peningkatan Kinerja Usaha Melalui Kemampuan Manajemen Serta Inovasi - Wibisono, Aryo (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2019)
MSMEs are an independent business organization and play an important role in increasing economic growth in a country. The contribution of MSMEs to employment in developing countries, especially Indonesia, has a significant impact in overcoming the problem of unemployment. The purpose of this study is to determine the development of MSMEs in Sumenep Regency. The results of this study will be used to see the development of MSMEs in the Sumenep Regency area. This study will use quantitative research methodology, namely data collection through questionnaires. The number of samples and population in this study was 41 by using multiple linear regression analysis. The results of this study found that management capabilities have an impact on innovation, and innovation has an impact on business performance, but management capabilities do not have an impact on business performance. Therefore, innovations need to be owned by MSME owners in order to improve the business performance of their MSMEs.